Personal Determinants of Mental Reliability of College Students in Learning Activities - Filatov, Denis (Journal of Education, Technology and Computer Science, 2021)
The paper deals with methodological, theoretical and practical foundations of the problem of mental reliability of a person performing an activity. The problem of personal determinants of reliability is considered. It is concluded that in Russian psychology “reliability” is an interdisciplinary and general scientific concept. The author points out that the study and analysis of this characteristic of the personality of college students makes it possible to arrange and manage professional development.